Distribution, sources and pollution status of Pb in indoor and outdoor dusts of Kerman City, SE Iran. Issue 1 (2nd January 2019) - Abbasnejad, Ahmad; Abbasnejad, Behnam
Abstract: The aims of this study were to explore the status of pollution and the temporal/spatial distribution of indoor and outdoor dust-Pb in the city of Kerman (SE Iran), located in a dry playa and arid climatic zone. Flat panes were laid at appropriate locations, in the indoor and the outdoor spaces of selected one-story houses in different areas of the city, to collect dust samples. Forty-two samples were taken and analyzed using the ICP-MS method. The measurements have shown that the outdoor dust-Pb concentrations varied from 23.7 to 275.2 mg kg −1, with a mean value of 71.8 mg kg −1, and indoor dust-Pb concentrations ranged from 47.6 to 150.2 mg kg −1, with a mean value of 89.6 mg kg −1 . Based on these measurements, Pb was enriched in the outdoor and the indoor dust samples up to 48.8 and 29.4 times, respectively. Dilution, as a result of prevalence of geogenic dust in the outdoor space, is expected to be the main cause of the temporal differences. This study has shown that the eastern part of the city is more polluted compared to the other parts, and, because of the stable air conditions, the concentration of Pb in the summer dust is higher than the other seasons.